Serum proteome‐wide identified ATP citrate lyase as a novel informative diagnostic and prognostic biomarker in pediatric sepsis: A pilot study. Issue 2 (30th December 2020) - Wang, Chunxia; Zhu, Xiaodong; Cui, Yun; Miao, Huijie; Xu, Yaya; Xiong, Xi; Tang, Xiaomeng; Shao, Lujing; Zhang, Yucai
Abstract: Introduction: ATP citrate lyase (ACLY) is involved in lipid metabolism and inflammatory response in immune cells. However, the serum level of ACLY and its clinical relevance in sepsis is totally unknown. Methods: We conducted a prospective pilot study in patients with sepsis admitted to pediatric intensive care unit (PICU) from January 2018 to December 2018. Results: Higher levels of ACLY were detected in sera of pediatric patients with sepsis than that of healthy children. The area under the receiver operating characteristic curve (AUC) of ACLY for diagnosis of sepsis was 0.855 (95% confidence interval [CI]: 0757–0.952), and an AUC of ACLY for predicting PICU mortality was 0.770 (95% CI: 0.626–0.915). ACLY levels ≤21 ng/ml on PICU admission predicted an unfavorable prognosis among patients with sepsis with a sensitivity of 87.5% and a specificity of 67.6%. Moreover, serum ACLY levels were correlated to platelet count, IL‐18 levels, and monocyte counts in pediatric patients with sepsis, implying the potential roles of ACLY in immunometabolic regulation in sepsis. Conclusions: ACLY is firstly identified in sera of patients with sepsis. Serum ACLY level is an additional diagnostic and prognostic biomarker in pediatric patients with sepsis. Abstract : ACLY is firstly identified in sera of patients with sepsis. Serum ACLY level is an additional diagnostic and prognostic biomarker in pediatric patients with sepsis.The relationship between serum ACLY and IL‐18 and underlying mechanisms involved in pathophysiology of sepsis need further study in the future.